Agronomic performance and beer quality assessment of twenty hop cultivars grown in Central Italy - Rossini, Francesco; Loreti, Paolo; Provenzano, Maria Elena; De Santis, Diana; Ruggeri, Roberto (Italian Journal of Agronomy, 2016)
Hop market and beer industry have always been of secondary relevance in Italy as compared to grape and wine sector. Hence, hop cultivars and the information for growing hops have been generated almost entirely from the major hop production countries. Identifying cultivars that perform well in Mediterranean environments is therefore essential to successfully start hop cultivation and breeding activity in this new growing region. To evaluate the intraspecific diversity of hop in Central Italy, 20 female hop genotypes with different origin were screened during three growing seasons (2013-2015) in an experimental hop yard. Cones yield, plant height and crop phenology were evaluated to determine which cultivars were best suited to the Mediterranean climate. Moreover, given the rising interest for the development of local beers with distinguishing aroma, a sensory analysis was performed and beers flavoured with locally produced and imported cones were compared. A significant diversity among cultivars was found for all parameters investigated. The results indicated that weather condition during flowering and development of cones markedly affected yield and plant height. Cones yield was negatively correlated with thermal time (r=–0.5, P<0.05) to harvest and positively with plant height (r=0.56, P<0.05). Cascade, Hallertauer Magnum, Hersbrucker Spat and Yeoman showed the best adaptability to the Mediterranean growing conditions as they were the top-performing cultivars across the three years. Sensory analysis evidenced the importance of cultivar selection as determining factor for flavouring properties of beers. In general, results showed that the origin of cones strongly affected the mouth feel of beers. More complex and appreciated aroma profiles were identified for beers flavoured with local cones than those hopped with commercial products.